2020
DOI: 10.1038/s41379-020-0629-6
|View full text |Cite
|
Sign up to set email alerts
|

The genetics of ductal adenocarcinoma of the pancreas in the year 2020: dramatic progress, but far to go

Abstract: The publication of the "Pan-Cancer Atlas" by the Pan-Cancer Analysis of Whole Genomes Consortium, a partnership formed by The Cancer Genome Atlas (TCGA) and International Cancer Genome Consortium (ICGC), provides a wonderful opportunity to reflect on where we stand in our understanding of the genetics of pancreatic cancer, as well as on the opportunities to translate this understanding to patient care. From germline variants that predispose to the development of pancreatic cancer, to somatic mutations that are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 232 publications
(376 reference statements)
3
24
0
1
Order By: Relevance
“…Over the last decade, comprehensive characterization of wellannotated tumor specimens has led to a better understanding of the key genomic alterations in PDAC, including somatic mutations in KRAS, TP53, CDKN2A, and SMAD4, and molecular classifications of tumors based on gene expression patterns (Thompson et al, 2020). In addition, these studies have revealed tumor-specific therapeutic targets (Balachandran et al, 2019;Golan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, comprehensive characterization of wellannotated tumor specimens has led to a better understanding of the key genomic alterations in PDAC, including somatic mutations in KRAS, TP53, CDKN2A, and SMAD4, and molecular classifications of tumors based on gene expression patterns (Thompson et al, 2020). In addition, these studies have revealed tumor-specific therapeutic targets (Balachandran et al, 2019;Golan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The first example we will give is a very simple one, but it nicely illustrates the power of an evolutionary approach. Pancreatic cancer runs in some families, and a number of the genetic loci associated with an increased risk of pancreatic cancer have been identified [6]. Some of these loci have been discovered using candidate gene or unbiased sequencing approaches such as whole genome and whole exome sequencing, while others have been found through genome-wide association studies (GWAS) ( Table 1) [6][7][8][9][10][11][12][13][14].…”
Section: Highly Deleterious Germline Variants Vs Variants With Smallmentioning
confidence: 99%
“…Sie helfen beispielsweise Samplingfehler bei Probeentnahmen aus Tumoren mit einem hohen Grad an Heterogenität (wie dem PDAC) oder Fehlbiopsien zu erkennen und korrekt zu interpretieren. So wird in Zeiten der personalisierten Therapie neben den klinischen und laborchemischen Parametern insbesondere auch eine Integration der radiologischen und (histo‑)pathologischen Parameter zum besseren Verständnis von (Pankreas‑)Karzinompatienten vorgeschlagen [ 26 ].…”
Section: Ausblickunclassified